PENINGKATAN PRODUKSI PUPUK KOMPOS DARI LIMBAH SAMPAH ORGANIK DI DESA KERTAWANGI MENGGUNAKAN TEKNOLOGI KONSORSIUM MIKRO ORGANISME LOKAL (MOL) BIO COMPOUND - Aldissain Jurizat (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2022)
Communities in Desa Kertawangi have a problem managing organic waste from plantation products. However, this case has become the subject of discussion among researchers, communities, and related stakeholders about how to speed up the process of producing compost from organic waste. The technology solution is to utilize the local micro-organism consortium (MOL) to accelerate the decomposition process of organic waste. After the demonstration, the community was enthusiastic about using it. The village's organic waste management unit has utilized this for composting the organic waste.